PTR2 peptide transporters in Fusarium graminearum influence secondary metabolite production and sexual development. Issue 5 (May 2017) - Droce, Aida; Sørensen, Jens Laurids; Sondergaard, Teis Esben; Rasmussen, Janus Jagd; Lysøe, Erik; Giese, Henriette
Abstract: Putative proton coupled di-peptide transporters, PTR2s, are found in filamentous fungi in different numbers and their function during fungal development and plant infection is unresolved. In Fusarium graminearum, the cause of head blight in cereals, we identified four putative PTR2 transporters ( FgPTR2A-D ). The genes did not cluster together in phylogenetic analyses and only FgPTR2A and FgPTR2C were able to complement a PTR2 deficient yeast mutant in uptake of di-peptides. All FgPTR2 s are continuously expressed throughout the fungal lifecycle, although at different levels. In silico analyses of existing expression-data show that FgPTR2B is found at higher levels than the others in planta and during sexual development. Deletion mutants of FgPTR2A, FgPTR2C, and FgPTR2D had a higher production of deoxynivalenol (DON) and zearalenone and lower production of fusarielin H than the wild type. Perithecium development was reduced in these mutants but unaffected by deletion of FgPTR2B . Conidia production was reduced in the FgPTR2B mutant and unaffected by deletion of the other PTR2 transporters. Sexual development and secondary metabolite production are known to be linked at the regulatory level and the results suggest that PTR2s are active in nitrogen turnover and thereby influence signal processes.